The Performance of Modified Conventional Still Distiller with a Coupled External Passive Condenser: An Experimental Study - Oni, Omolara; Adam, Hamzah; Oguike, Raphael (PUI BiGME Universitas Jambi, 2025)
Solar radiation plays an important role in the desalination process due to its abundance in areas with potable water shortage and also occupies an important position in renewable energies due to simplicity of application. Still distiller is viewed by researchers as suitable source of potable water because of low cost of fabrication, easy operation and zero emission technology. Studies by researchers is geared towards exploring new models to enhance the efficiency of solar stills and increase the production rates. The main aspiration of this work is to experiment the effect of incorporating a passive condenser into a modified conventional solar still to enhance daily productivity rate. It has been found that modified passive still distiller coupled with external condenser gives about 11.85% higher production rate as compared to the modified conventional still distiller. Daily and accumulated distillate yield for the still distillers have been studied and analyzed. As a result of the findings, the researchers recommend the sawdust padding around still distillers can maximize productivity leading to efficient water distillation in regions where that require still distiller usage. This recommendation has desired result of enhancing access to potable water in areas with water scarcity and do contribute to sustainable and cost-effective water purification method.